Four new species of caddisflies (Trichoptera: Polycentropodidae, Psychomyiidae, Hydropsychidae, Odontoceridae) from Khao Nan and Tai Rom Yen National Parks, southern Thailand - Suwannarat, Nannaphat; Malicky, Hans; Laudee, Pongsak (Zootaxa, 2020)
Males of four new species of caddisflies, Polyplectropus hofmaierae n. sp. (Polycentropodidae), Eoneureclipsis chinachotiae n. sp. (Psychomyiidae), Hydropsyche khaonanensis n. sp. (Hydropsychidae), and Lannapsyche tairomyenensis n. sp. (Odontoceridae) are described and illustrated. Polyplectropus hofmaierae n. sp. is distinguished from other species by the shape of the apical end of its inferior appendages and its sharp intermediate appendages. The posterior edges of their inferior appendages run slanting to the ventrodistal point and are densely covered by short and stiff bristles. Eoneureclipsis chinachotiae n. sp. is differentiated by characters of its phallus, as the first two thirds of its length are slender and slightly curved. The distal part has a dorsal hump with a very slender thread on its caudal edge and is slightly bent downward and dilated. Hydropsyche khaonanensis n. sp. can be differentiated from the other species by its phallus, in which the two apicolateral lobes in ventral view have rounded outer edges. Lannapsyche tairomyenensis n. sp. can be separated from the others by characteristics of the dorsal view of segment IX and the harpago of its inferior appendages. Segment IX is triangular with distinctly convex preanal appendages along the posterior edge of this segment, and the harpago and subapical lobes are relatively similar in shape and length.